Project Risk Mitigation in Construction Projects (Case Study of Medan Station Building and Emplacement Development Project Phase II) - Hardiputra, Andrew; Noviaristanti, Siska; Rahadian, Dadan (Jurnal Manajemen Indonesia, 2025)
The success of a construction project can be determined by the achievement of targets in terms of time, cost and quality. The data shows that several construction projects undertaken by Waskita Karya experienced delays in the completion of work and increased costs. Risk mitigation has an important role in project control from the start in order to find out the causes of risk and how to handle them. This study aims to determine the risk mitigation strategy in the Medan Station Building and Emplacement Development Project Phase II. The research phenomenon is explored using a case study method through a quantitative approach. Data collection techniques are interviews, observation, and documentation. Construction risk factors include internal, external and project risks. More in-depth studies are limited to project risks, which have a direct impact on time, cost, quality, construction and technology. The results showed that 43 relevant risk factors had been identified. Obtained 11 risk factors with a very high level of risk, including (1) delay in handing over the project to the owner, (2) failure to achieve the productivity plan for the contractor's equipment, (3) delay in land acquisition, (4) delay in finalizing the design, (5) increase in BK/PU, (6) increase in material prices, (7) waste material exceeding plan, (8) potential for extreme weather to hinder project implementation, (9) there are existing utilities, buildings, or other objects that need permits in in terms of demolition in the work area, (10) delays in fulfilling labor and work tools, (11) innovative working methods.